2019
DOI: 10.1193/033017eqs056m
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic Displacement Spectra and Its Utilization of DDB Design for Seismic Isolated Bridges Subjected to Near-Fault Pulse-Like Ground Motions

Abstract: A variety of research has focused on the inelastic displacement demand of a single degree of freedom (SDOF) system when subjected to near-fault pulse-like ground motions, in which the concerned ductility, μ, is typically lower than ten for normal structures. However, for seismic isolated structures that are more prone to large displacement, the corresponding research is limited. The purpose of this paper is to investigate the inelastic displacement spectra of an SDOF system with μ ranging from 5 to 70 and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A set of near-fault earthquake records with a large long pulse from 26 different earthquake events, which is downloaded from the strong motion database of the Pacific Earthquake Engineering Research (PEER) Center, is shown in Table 1. These selected records are based on the pulse characterization algorithm proposed by Shahi and Baker (2011, 2014), and they have been widely used in previous studies (Baker, 2007; Chopra and Chintanapakdee, 2001; Iervolino et al, 2012; Khoshnoudian and Ahmadi, 2015; Rahgozar et al, 2016; Ruiz-Garcia, 2011; Wen et al, 2014; Wu et al, 2019). The rupture distance (closest distance from the site to fault rupture plane) of these motions covers a range of less than 20.0 km.…”
Section: Ground Motions Used In This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A set of near-fault earthquake records with a large long pulse from 26 different earthquake events, which is downloaded from the strong motion database of the Pacific Earthquake Engineering Research (PEER) Center, is shown in Table 1. These selected records are based on the pulse characterization algorithm proposed by Shahi and Baker (2011, 2014), and they have been widely used in previous studies (Baker, 2007; Chopra and Chintanapakdee, 2001; Iervolino et al, 2012; Khoshnoudian and Ahmadi, 2015; Rahgozar et al, 2016; Ruiz-Garcia, 2011; Wen et al, 2014; Wu et al, 2019). The rupture distance (closest distance from the site to fault rupture plane) of these motions covers a range of less than 20.0 km.…”
Section: Ground Motions Used In This Studymentioning
confidence: 99%
“…Since then, more and more attention has been paid to the inelastic response spectra (Bojórquez et al, 2012; Boore and Akkar, 2003; Chan-Anan et al, 2016; Cuesta and Aschheim, 2001; Elghadamsi and Mohraz, 1987; Faccioli and Villani, 2009; Ganzerli et al, 2000; Gupta, 1990; Lam et al, 2000a, 2000b; Lu and Wei, 2008). Moreover, the emerging concepts of the performance-based design require a quantitative understanding of the inelastic response spectra for different structure types (Bozorgnia et al, 2010; Wu et al, 2019; Zamora and Riddell, 2011; Zhai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In 1960, Veletsos and Newmark (1960) studied and defined the inelastic displacement ratio spectra for the first time. Since then, scholars have performed plenty of statistical analysis on the inelastic displacement ratio spectra of different nonlinear structures through time-history analysis, and proposed different prediction formulas (e.g., Miranda 2001;Wen et al 2014;Hassani et al 2018;Bararnia et al 2018;Yaghmaei-Sabegh et al 2017;Konstandakopoulou et al 2020;Wu et al 2019). Currently, research on the inelastic ratio spectra mainly focuses on common elastic-plastic structures, and the constitutive models of these structures mainly include the bilinear model, elastic-plastic model, and degradation model.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the directivity effect and fling step effect are concerned, since they often cause the velocity pulse and large-scale permanent ground translation (Mavroeidis and Papageorgiou, 2002). In addition, the inelastic structural response demands induced from NFGMs differ significantly from those recommended in design specifications based on FFGMs (Baltzopoulos et al, 2016;Wu et al, 2019). In the last two decades, some studies have been carried out on the residual displacements of the SDOF systems under the NFGMs.…”
Section: Introductionmentioning
confidence: 99%